Transformation of the socio‐ecological situation relating to HIV in the North Caucasus Federal District under the influence of external migration - R. V. Dmitriev (Юг России: экология, развитие, 2019)
Aim. The aim of the study is to identify the degree of external threat relating to the  spread of HIV infection by migrants in the North Caucasus Federal District of Russia. Material and Methods. Systemic, comparative geographical, geographic and statistical research methods were applied, as well as MS Excel and SPSS Statistics software packages. The database was created for the periods 1997‐2000, 2003‐2006,  2007‐2010 and 2011‐2015. Four main (aggregated) groups of indicators were selected.   Results. A hierarchical cluster analysis was undertaken on groups of indicators (the  current situation in states studied regarding the spread of HIV, the flow of migrants  from these states to the North Caucasus Federal District as a whole and its differentiation according to chronological and chorological characteristics) which made it  possible to aggregate the countries of Asia and Africa into four groups according to  threat level of the spread of HIV infection for the North Caucasus Federal District:  (1) extremely high (post‐Soviet states of the Caucasus and Central Asia [excepting  Turkmenistan]); (2) high (states of the eastern Mediterranean [excepting Lebanon],  as well as Afghanistan and Turkmenistan); (3) countries of a medium degree of  threat (most of the countries of sub‐Saharan Africa, Southeast Asia [except Vietnam, Laos, Cambodia, the Philippines and Brunei], as well as Pakistan); (4) low (all  states).   Conclusion. Despite the greater spread of HIV in African states compared with  Asian states, it is the latter ‐ especially those formerly part of the USSR ‐ that pose  the greatest threat to the North Caucasus Federal District with regard to the spread  of HIV by migrants. Almost every state of origin of the majority of migrants infected  with HIV has “its own” preferred destination in the North Caucasus Federal District,  to which their inflows are oriented.